INCOME INEQUALITY – PERSPECTIVES FROM THE MAIN SCHOOLS OFECONOMIC THOUGHT - Bratoeva-Manoleva, Silviya (E-Journal VFU, 2025)
In recent decades, we have witnessed a growing income inequality, which has become one of the most discussed topics, raising concern within society. Understanding the mechanisms of income formation, distribution and redistribution has become exceptionally crucial for this reason. The article aims to present the various perspectives of major economic theories on income inequality. The analysis reveals the complexity and multifaceted nature of the concept of income inequality, contributing to a more in-depth assessment of the forces contributing to its formation.